China's big dams. - Sweet, W.
China accounts for nearly half the worlds big dams, yet authorities there say that more than four-fifths of the country's hydroelectric potential remains unexploited. Accordingly, whether or how to build more dams there and elsewhere, and how to deal with the side-effects of dams already built or under construction, are big issues with regional and global implications. Dams have a role to play in reducing greenhouse emissions. It is generally safe to assume that electricity generated by a dam will have significantly less impact on climate change than the same amount generated from coal. Yet, despite their evident benefits, big dams are regarded with great suspicion by environmentalists and human rights activists. Because of an ever-shriller debate worldwide about their merits and defects, international lending agencies are increasingly loathe to support them. The reasons are manifold including displaced population, unexpected sedimentation patterns and flow changes, and the richest landowners taking the majority of water meant for irrigation. This paper describes the Xiaolangdi dam and the environmental and social issues surrounding its construction and operation. The implications for the Three Gorges Dam are also discussed
Keywords: China; Three Gorges Dam; Xiaolangdi dam; Dams; Displaced population; Environmental issues; Environmentalists; Flow changes; Greenhouse emissions reduction; Human rights activists; Hydroelectric potential; International lending agencies; Social issues; Unexpected sedimentation patterns